On the dynamical coupling between atmospheric blocks and heavy precipitation events: A discussion of the southern Alpine flood in October 2000 - Lenggenhager, Sina; Croci-Maspoli, Mischa; Brönnimann, Stefan; Martius, Olivia (Quarterly Journal of the Royal Meteorological Society, 2019)
In October 2000, a high‐impact lake flood event occurred in southern Switzerland. During the month prior to the flood event three heavy precipitation events (HPEs) occurred. The first two events preconditioned the catchment and brought the lake close to its flood level. During the third event the lake level rose above the flood threshold. At the same time, anomalously high blocking activity was observed in the northern North‐Atlantic/European region. This study describes the synoptic development during the month prior to the flood and investigate the role of atmospheric blocking for the formation of the HPEs using ERA‐Interim data. Atmospheric blocks are identified as persistent negative potential vorticity (PV) anomalies in the upper troposphere. All three heavy precipitation events were forced by upper‐level equatorward elongated streams of stratospheric high‐PV air (PV streamers). These PV streamers formed in the strong deformation field upstream and downstream of single blocks or in between two blocks. During the third and most persistent heavy precipitation episode the eastward propagation of the PV streamer was prevented by a downstream block for several days leading to a stationary upper‐level north‐eastward flow and a prolonged period of heavy precipitation over the catchment. The study identifies and quantifies a potential feedback between heavy precipitation and blocks via diabatic depletion of PV. It is shown that a substantial fraction of the diabatically modified low PV air (63%) that reached and strengthened the blocks over the Atlantic and Europe during this month experienced heating in HPE areas.